Analysis public sentiment on freeport’s sustainability and its impact on the Pestapora Festival: A social media analysis (BIS Humanities and Social Science, 2026)
Pestapora, one of the biggest annual music festivals in Jakarta held by the promoter Boss Creator, faced controversy after announcing PT Freeport Indonesia as one of their sponsors. The partnership drew public criticism over Freeport’s environmental and human rights track record in Papua. This study examines how public sentiment toward Freeport’s sustainability efforts affects the perception of Pestapora on social media. Using qualitative content analysis, comments from Instagram posts on Pestapora’s official account and from artists who withdrew from the lineup, were analysed. Guided by Audience Reception Theory from Stuart Hall, comments were categorized as dominant, negotiated, or oppositional reading to analyse how context shapes sentiment. Findings show audience responses were predominantly negotiated, showing that digital audiences actively reinterpret messages through ethical and cultural considerations. Individual actions received more dominant readings than institutional communication, indicating higher perceived moral credibility toward personal decisions in sponsorship controversies.